Vaping and psychotic experiences among college students in the United States. (1st October 2021) - Oh, Hans; Banawa, Rachel; Lee, Jungeun Olivia; Zhou, Sasha; Huh, Jimi
Highlights: Roughly 14 % of students in the sample reported psychotic experiences over the past year. About 14–15 % of students reported vaping over the past month. Students who vaped were more likely to have reported psychotic experiences. This association remained significant after adjusting for other substance use and mental health. Abstract: Aim: While cigarette and marijuana use has been linked to psychotic experiences, few empirical studies have examined the relation between vaping and psychotic experiences. Methods: We analyzed data from the Healthy Minds Survey (September 2020 – December 2020; N = 29, 232 students from 36 universities), and used multiple logistic regression models to examine the associations between vaping over the past 30 days and psychotic experiences over the past 12 months, adjusting for age, gender, and race/ethnicity. We then additionally adjusted for cigarette and marijuana use, as well as depression and anxiety. Results: Roughly 14 % of students in the sample reported psychotic experiences over the past year, and around 14–15 % of students reported vaping over the past month. In multiple logistic regression models, vaping was significantly associated with psychotic experiences (aOR 1.88; 95 % CI: 1.63–2.18). This association attenuated but remained statistically significant even after adjusting for any cigarette use and marijuana use, and after adjusting for depression and anxiety. Conclusions: Among college students, vaping was significantly associated with psychotic experiences, even after accounting for simple measures of cigarette and marijuana use, and mental health problems, calling for more prospective studies to examine the association.